PENGUATAN KESADARAN SERTA TINDAKAN PREVENTIF TERHADAP BAHAYA KANKER DI KPPN PUTUSSIBAU KALIMANTAN BARAT - Lily Khairani; Hamzah Irfanda (Universitas Sumatera Barat, 2026)
Cancer is a non-communicable disease that poses a serious threat to public health, including in government agencies' workplaces. Low awareness and preventive measures against the dangers of cancer can impact the quality of life and work productivity. This Community Service activity aims to strengthen awareness and encourage preventive measures against the dangers of cancer among employees of the Putussibau KPPN, West Kalimantan. The method used was Participatory Action Research (PAR) which was implemented through the stages of planning, action, observation, and reflection with the active participation of partners. Data collection was carried out through participatory observation, interactive discussions, and the distribution of questionnaires before and after the health education activity. The data obtained were analyzed using qualitative descriptive analysis with the stages of data reduction, data presentation, and drawing conclusions. The results of the activity showed an increase in employee knowledge and awareness regarding cancer risk factors, the importance of early detection, and the implementation of healthy lifestyle behaviors in the workplace. In addition, participants demonstrated a positive attitude and commitment to implementing preventive measures on an ongoing basis. In conclusion, strengthening awareness through PAR-based health education is effective in encouraging changes in employee knowledge, attitudes, and preventive commitment. This activity has the potential to provide a real contribution to the formation of a healthy work culture as an effort to prevent cancer in government agencies